2020
DOI: 10.1371/journal.pone.0240321
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and clinicopathological significance of long noncoding RNA MALAT-1 expression in patients with non-small cell lung cancer: A meta-analysis

Abstract: Background Although expression of long non-coding RNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT-1) in tumor tissues has been assessed in several malignancies. However, the association between lncRNA MALAT-1 expression and prognosis or clinicopathological feature remains controversial. Therefore, we conducted a meta-analysis to verify whether lncRNA MALAT-1 expression was associated with prognosis or clinicopathological features in patients with non-small cell lung cancer (NSCLC). Methods We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…26 A meta-analysis of patients with non-small-cell lung cancer showed that high expression of MALAT-1 in tumor tissues was associated with shorter overall survival. 27 Similarly, the role of MALAT-1 in a variety of autoimmune diseases should not be ignored. MALAT-1 inhibited the inflammatory response of articular chondrocytes induced by IL-1β by blocking the activation of the JNK signaling pathway, enhancing chondrocyte proliferation, and inhibiting chondrocyte apoptosis and extracellular matrix degradation.…”
Section: Discussionmentioning
confidence: 99%
“…26 A meta-analysis of patients with non-small-cell lung cancer showed that high expression of MALAT-1 in tumor tissues was associated with shorter overall survival. 27 Similarly, the role of MALAT-1 in a variety of autoimmune diseases should not be ignored. MALAT-1 inhibited the inflammatory response of articular chondrocytes induced by IL-1β by blocking the activation of the JNK signaling pathway, enhancing chondrocyte proliferation, and inhibiting chondrocyte apoptosis and extracellular matrix degradation.…”
Section: Discussionmentioning
confidence: 99%
“…It is highly important that MALAT1 expression was not detected in 73.4% of plasma samples after DNAse treatment. Τhis observation, combined with the lack of DNAse treatment, may explain the ambiguous results of various studies that characterized MALAT1 either as oncogene or as tumor suppressor and consequently report that its expression is upregulated or downregulated, respectively [ 21 , 30 , 49 , 50 ]. One of the few studies that performed DNAse treatment before quantification of MALAT1 expression demonstrated that MALAT1 is a metastasis-suppressing lncRNA rather than a metastasis promoter lncRNA in breast cancer [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…overexpression of lncRNA-MALAT1 in the serum exosomes of NSCLC patients was positively correlated with the tumor stage and lymph node metastasis (32). Moreover, knockdown of lncRNA-MALAT1 suppressed the progression of NSCLC by inhibiting growth and metastasis and facilitating apoptosis, possibly by upregulating miR-185-5p and decreasing the expression of MDM4 in NSCLC (33).…”
Section: Any Additional Considerations If Applicable N/amentioning
confidence: 91%